The Hammer and the Dance of Cell Cycle Control. Issue 4 (April 2021) - Panagopoulos, Andreas; Altmeyer, Matthias
Abstract : Cell cycle checkpoints secure ordered progression from one cell cycle phase to the next. They are important to signal cell stress and DNA lesions and to stop cell cycle progression when severe problems occur. Recent work suggests, however, that the cell cycle control machinery responds in more subtle and sophisticated ways when cells are faced with naturally occurring challenges, such as replication impediments associated with endogenous replication stress. Instead of following a stop and go approach, cells use fine-tuned deceleration and brake release mechanisms under the control of ataxia telangiectasia and Rad3-related protein kinase (ATR) and checkpoint kinase 1 (CHK1) to more flexibly adapt their cell cycle program to changing conditions. We highlight emerging examples of such intrinsic cell cycle checkpoint regulation and discuss their physiological and clinical relevance. Highlights: Shutdown of cell cycle progression by checkpoint activation is the exception rather than the norm when cells face physiological levels of replication stress. In response to endogenous replication stress, cells use tunable deceleration and brake release mechanisms under the control of the ATR and CHK1 kinases for timely completion of DNA duplication. Intrinsic checkpoint activation, maintenance, and recovery represent a continuum, which is modulated by CHK1 phosphorylation and ubiquitin-dependent proteasomal degradation. Sharp cell cycle transitions, in which one cell cycle phase is fully concluded before the next one begins, can be blurred due to a balancing act between genome integrity maintenance and an urge for cell cycle completion. Deviations from ordered cell cycle phase transitions promote cancer, with therapeutic opportunities for cell cycle checkpoint kinase inhibitors.